Safety of Phenobarbital in Neonates with HIE - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Phenobarbital treatment (20 mg/kg iv) had no significant effect on cerebral blood flow or blood pressure and heart rate, measured 60 min after a loading dose, in 7 term newborn infants with mild to moderate hypoxic ischemic encephalopathy examined in the Dept of Paediatrics, Alborg Hospital, Denmark.